Molecular physics: Theoretical principles and experimental methods - Demtröder, Wolfgang (Wiley-VCH-Verlag, 2012)
The richly illustrated book comprehensively explains the important principles of diatomic and polyatomic molecules and their spectra in two separate, distinct parts. The first part concentrates on the theoretical aspects of molecular physics, such as the vibration, rotation, electronic states, potential curves, and spectra of molecules.